Improving reproducibility and translational potential of mouse models: lessons from studying leishmaniasis - Nateghi-Rostami, Mahmoud; Lipoldová, Marie; Sohrabi, Yahya (Frontiers in immunology, 2025)
Leishmaniasis is a complex disease caused by protozoan parasites of the genus Leishmania, which are transmitted by phlebotomine sand flies. The clinical manifestations of leishmaniasis are diverse, ranging from self-healing cutaneous lesions to fatal systemic disease. Mouse models are instrumental in advancing our understanding of the immune system against infections, yet their limitations in translating findings to humans are increasingly highlighted. The success rate of translating data from mice to humans remains low, largely due to the complexity of diseases and the numerous factors that influence the disease outcomes. Therefore, for the effective translation of data from murine models of leishmaniasis, it is essential to align experimental conditions with those relevant to human infection. Factors such as parasite characteristics, vector-derived components, host status, and environmental conditions must be carefully considered and adapted to enhance the translational relevance of mouse data. These parameters are potentially modifiable and should be carefully integrated into the design and interpretation of experimental procedures in Leishmania studies. In the current paper, we review the challenges and perspective of using mouse as a model for leishmaniasis. We have particularly emphasized the non-genetic factors that influence experiments and focused on strategies to improve translational value of studies on leishmaniasis using mouse models.
Keywords: Animals; experimental analysis; human leishmaniasis; translační biomedicínský výzkum; Leishmaniasis; Reproducibility of Results; lidé; leishmanióza; Mice; myši; reprodukovatelnost výsledků; modely nemocí na zvířatech; Translational Research, Biomedical; translation; Leishmania; Disease Models, Animal; experimental conditions; reproducibility of data; zvířata; mouse model; influencing factor; Humans